Analysis of Student Conceptions based on Cognitive Style on Newton Law Understandings - Mustofa, Hisbulloh Als; Zain, Zahida Aliatu; Tsania, Hartami; Azman, Mohamed Nor Azhari; Marmoah, Sri; Masfuah, Siti (Universitas Negeri Semarang, 2024)
Differences in students’ cognitive style aspects allow for differences in students’ conceptions of their understanding of Newton’s laws. This study aims to determine the profile of students’ conceptions in-depth based on their cognitive styles. This research used a qualitative method with a descriptive phenomenological design involving cognitive style tests with GEFT (Group Embedded Figured Test) on 30 students to be categorized based on their cognitive styles. From the 30 participants, three strongly field-dependent and three strongly field-independent students were selected. Six selected students were diagnosed using a four-tier diagnostic instrument for their understanding and conceptions. Semi-structured interviews were also conducted to investigate the students’ conceptions in depth. This study concludes that field-independent (FI) students frequently display an inclination toward analytical thinking by self-exploring. However, they frequently experience difficulties in analyzing concepts without a solid foundation in physics, which can result in certain theoretical misconceptions. Conversely, field-dependent (FD) students can receive a broader range of information but demonstrate difficulties in analytical tasks, such as interpreting graphs and establishing causal relationships between physical quantities, which can result in correlational misconceptions. To rectify this misconception, it is imperative to implement a bespoke pedagogical strategy that integrates efficacious elucidations, tangible exemplifications, structured scaffolding, inquiry, and methodical practical exercises.